Examination of Xanthan Production on Biodiesel Industry Effluent-based Medium in Lab-scale Bioreactor - Ida Zahović; Jelena Dodić; Damjan Vučurović; Bojana Bajić; Siniša Dodić; Zorana Trivunović
Xanthan is microbial polysaccharide with outstanding rheological properties, non-toxic nature, biodegradability, and biocompatibility. This biopolymer is widely used in food, biomedical, pharmaceutical, petrochemical, chemical and textile industry. Industrial xanthan production is generally conducted by aerobic submerged cultivation of Xanthomonas campestris strains on the media with glucose or sucrose under optimal conditions. Results from previous research indicate that xanthan can be successfully produced on media containing crude glycerol from biodiesel industry by different Xanthomonas species. The aim of this study was to examine the course of xanthan biosynthesis by the reference strain X. campestris ATCC 13951 in lab-scale bioreactor on medium containing crude glycerol generated in domestic biodiesel factory. The bioprocess was monitored by the analysis of cultivation medium samples taken in predetermined time intervals, and its success was estimated based on the xanthan concentration in the medium, separated biopolymer average molecular weight and degree of nutrients conversion. At the end of bioprocess, cultivation medium contained 12.34 g/L of xanthan with the average molecular weight of 3.04∙105 g/mol. Within this study, the achieved degree of glycerol, total nitrogen and total phosphorous conversion were 75.91%, 53.27% and 38.96%, respectively.